Issues in counselling - Mokhtar, Halimatun Halaliah (Universiti Putra Malaysia Press, 2012)
In Malaysia, guidance and counseling are continuously developing in various ways. First, many are interested in making guidance and counselling their professional career. We also have individuals who wish to extend a helping hand to the community, helping others in one way or another who choose to become volunteers. Apart from the above, we have individuals who choose to teach others to become practicing counsellors or academicians and there are others whether willingly or reluctantly become the “receivers” of professional service. On the part of the service providers, knowledge and skills are required guide and help others live a better life. On the part of the academicians, knowledge and skills are the necessary tools to be conveyed to their studttents. On the part of the clients, knowledge and skills could give them the strength to cope with their issues and challenges in life. It is hoped that this book will enlighten the readers with the various issues and challenges related to guidance and counselling. As professional helpers, we need to be fully prepared with the necessary tools, be aware of issues and challenges, when giving a helping hand.